Effect of Annona muricata L. Leaf Ethanol Extract in CCl4 Hepatitis Rat Model - Kuswinarti Kuswinarti; Ilham Asrori Azka; Dwi Prasetyo (Althea Medical Journal, 2021)
Background: Liver can be damaged by various factors, including the oxidative stress mechanism. This damage can be inhibited by the application of anti-oxidant. The Annona muricata L. leaf is known to have antioxidant properties. This study aimed to explore the effect of Annona muricata L. leaf extract against hepatitis in rats.Methods: An experimental study was performed on 25 male Wistar rats that were given Annona muricata L. leaf ethanol extract at 200 mg/kgBW, 400 mg/kgBW, and 600 mg/kgBW for eight days. The CCl4 was administrated on the eighth day and the rats were laparotomized on the next day. The average number of normal hepatocytes was counted in one field of view. This study was conducted at the laboratory of Pharmacology and Therapy of the Faculty of Medicine, Universitas Padjadjaran in September–October 2012.Results: The negative control group showed an intact cell membrane, homogenous cytoplasm, and round nucleus, whereas the positive control group showed necrosis marked by a ruptured cell membrane, vacuolated cytoplasm, and degenerated nucleus. The average number of normal hepatocytes counted in the negative control and the positive group was 404.91±34.09 cells and 23.16±7.84 cells, respectively. In the treatment group, the normal hepatocytes were 95.91±20.96 cells (200 mg/kgBW), 74.53±13.59 cells (400 mg/kgBW) and 46.84±8.46 cells (600 mg/kgBW). Statistically significant inhibition was observed (p<0.05).Conclusions: The Annona muricata L. leaf ethanol extract can inhibit liver tissue damages in hepatitis model rats, possibly due to the presence of acetogenins as an anti-oxidant agent.